TRADISI SUROHAN DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS - Prihatanti, Vidya Wahyu (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to describe the implementation of the Surohan tradition, and cultural meaning in food offerings in the Surohan Tradition, and its relevance to the learning of Indonesian Language and  Literature in Senior High Schools. Research data can be obtained using observation, documentation, and interview methods. The subjects in this study were the elders of Seloliman Village, residents of Seloliman Village and MA Asy-safiiyah teachers. The type of research used in this study used a qualitative descriptive research method. The data validation technique used is the triangulation of data sources and methods. There are three data analysis techniques used, namely, data reduction, data verification, and data display. The results of the study show that there are two processes in implementing the Surohan tradition in Seloliman Village. The first process is preparation and the second process is implementation. The forms of food offerings in the Surohan tradition carried out in Seloliman Village have 19 types of food offerings, namely cone, urap-urap, roast chicken, red porridge, white, black, yellow porridge and bubur sengkolo, jajan pasar, plantain, banana kluthuk, setaman flower water and 18 kinds of ancak fruit. The meaning of food  is analyzed using cultural meaning. The study of Surohan tradition and food offerings in it can be used as relevance to the learning of Indonesian Language and Literature in Senior High Schools, which is a reference for teaching materials specifically in the material structure of exposition text in  odd semester X class. Keywords: Ethnolinguistics, Surohan Tradition, Indonesian Language and Literature Learning in High School.